Filarial nematode infection in eclectus parrots (Eclectus roratus) in Taiwan. Issue 2 (4th March 2017) - Huang, Yen-Li; Tsai, Shinn-Shyong; Thongchan, Duangsuda; Khatri-Chhetri, Rupak; Wu, Hung-Yi
ABSTRACT: A total of 166 psittacines belonging to 22 species were received by the Animal Hospital of National Pingtung University of Science & Technology (NPUST) from 2013 to 2015. Only eclectus parrots ( Eclectus roratus ) were identified as hosts for microfilariae. All eclectus parrots were adult birds and had been kept in Taiwan for more than three years. The relevance of filariae to eclectus parrots is evident as indicated by the 35.7% (5/14) infection rate. At necropsy, adult filarial nematodes 57–75 mm in length and 0.4–0.7 mm in width were found in the hepatic veins. The microfilariae were 170–230 μm in length. Histopathological examination confirmed that eggs and larvae were observed in the ovaries and uteri of female filariae. These nematodes were closely related to an unidentified Filaria sp. (KJ612514.1) as indicated by polymerase chain reaction (PCR) analysis and phylogenetic analysis of nucleotide sequences from 18S ribosomal DNA gene (18S rDNA), mitochondrial cytochrome c oxidase subunit 1 (COX1) gene, and internal transcribed spacers 1-5.8S ribosomal DNA gene (ITS 1-5.8S rDNA). However, structurally the filarial nematodes were similar to that of the Pelecitus sp. Eclectus parrot species are important pet birds and are highly traded, resulting in high uncertainty of the origin of the parasite infection. This study is the first of its kind to report the presence and potential impact of filarial nematode infection on eclectus parrots, suggesting parasite inspection prior to the international trade of these pet birds.